2006
DOI: 10.1002/chin.200649117
|View full text |Cite
|
Sign up to set email alerts
|

A Route to Regioselectively Functionalized Carbazoles, Dibenzofurans, and Dibenzothiophenes Through Anionic Cyclization of Benzyne‐Tethered Aryllithiums.

Abstract: lithiums. -(SANZ*, R.; FERNANDEZ, Y.; CASTROVIEJO, M. P.; PEREZ, A.; FANANAS, F. J.; J. Org. Chem. 71 (2006) 16, 6291-6294; Dep. Quim., Fac. Cienc., Univ. Burgos, E-09001 Burgos, Spain; Eng.) -Jannicke 49-117

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In 2006, Fananas group [7] found that the treatment of 2-fluorophenyl 2-iodophenyl thioether with 3.3 equiv. of t-BuLi, which further reacted with selected electrophiles, gave rise to functionalized dibenzothiophene derivatives (Scheme 1).…”
Section: C-x Cleavage For Dibenzothiophenes Synthesismentioning
confidence: 99%
“…In 2006, Fananas group [7] found that the treatment of 2-fluorophenyl 2-iodophenyl thioether with 3.3 equiv. of t-BuLi, which further reacted with selected electrophiles, gave rise to functionalized dibenzothiophene derivatives (Scheme 1).…”
Section: C-x Cleavage For Dibenzothiophenes Synthesismentioning
confidence: 99%
“…The most commonly used route to 1functionalized dibenzothiophenes is based on an elegant intramolecular anionic cyclization developed by Sanz and co-workers (Equation 1, Scheme 1). 8 Thiophenol 1a is converted to benzyne precursor 2a which undergoes an intramolecular anionic cyclization to 1-lithiodibenzothiophene 3a-Li, which can be quenched with electrophiles. Pummerer-based approaches beginning with cross-coupling of 4a to form biaryl 4b, which can undergo oxidative conversion to 1-functionalized dibenzothiophene 3b (Equation 2, Scheme 1).…”
Section: Scheme 1 Representative Syntheses Of 1-substituted Dibenzotmentioning
confidence: 99%
“…Spectral data agreed with literature values. 8 1 H NMR (500 MHz, CDCl3): δ 7.90 (dd, J= 7.9, 1.4 Hz, 1H), 7.34-7.31 (m, 1H), 7.13 (dd, J= 7.9, 1.5, 1H), 7.06-6.98 (m, 2H), 6.93-6.84 (m, 3H), 3.24 (s, 3H). 13…”
Section: N-(2-fluorophenyl)-n-(2-iodophenyl)-methylamine (8b)mentioning
confidence: 99%
“…In the fragmentation of their molecular ions using atmospheric pressure chemical ionization (APCI) tandem mass spectrometry (MS/MS) in positive ion mode, the positively charged biradicals of diphenyl sulfides were generated by elimination of iodine radicals. Although considerable efforts have been dedicated to investigating the fragmentation of various sulfur‐containing compounds, the dissociation of the positively charged biradicals of diphenyl sulfides has not been systematically discussed.…”
mentioning
confidence: 99%